Wanted: the book equation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
To fully promote the publishing sector in ACP countries, and in particular its role in information for agricultural and rural development, there is a need to convince investors, whether internal or external, statal or private, of the value of a book...